Inclusion of Digital Citizenship Skills in the Modified Educational Syllabi at Ha’il University: A Study in Teachers’ Perspective - Alotaibi, Wadha Shabib Ali (Journal of Ecohumanism, 2024)
In the wake of Covid-19 pandemic and the educational scenario shifting towards online teaching, universities brought about several modifications in their courses to accommodate online dissemination. These changes inspired learners and teachers to acquire the traits of digital citizenship (DC) skills. The present study investigates the perspectives of teaching staff at Ha’il University, Saudi Arabia, on the degree of inclusion of digital citizenship skills in the modified educational syllabi. In a mixed methods study, teachers' perspectives on the topic were collected from 227 participants. The data were collected through a survey questionnaire and statistically analysed using SPSS. To check the differences across variables, the following variables were used: academic degree, professional experience, and academic track. The obtained results showed that the teaching staff displayed a medium degree of satisfaction with the inclusion of DC skills in the educational syllabi. No significant differences between the means of responses of the study sample were observed (p> 0.05). The study findings have implications for instructors and learners. The researchers recommend further research in the area, and it is essential that training courses are conducted to increase the awareness of DC skills to develop digital content and to maximize the use of ICT tools especially in the light of the covid-19.